Variabilidade espaço-temporal de nutrientes foliares e produtividade do café conilon - Cezana, Diego Capucho (2014)
Precision agriculture brought tools that allow us to consider the plants a crop, not as a homogeneous environment, but in all its variability. Tools such as kriging the semivariogram and enable the construction of maps by interpolation of sample points that have spatial dependency between them, thereby causing, if known points in the sampling grid , without the need for sampling. The objective of applying geostatistics to coffee crop and investigate the spatial variability of attributes related to plant productivity, foliar N, P, K, Ca, Mg, Fe, Zn, Cu, Mn and B making estimates using the kriging technique presumes spatial variability and identify interrelationships of these attributes in space. The study was conducted on a commercial crop Conilon coffee variety called Bamburral, under irrigation, micro spray, in São Mateus state of Espírito Santo - Brazil. The experimental area has dimensions of 100x115 m, where we sampled a grid of 100 points with a minimum distance of 2 m between them. The crop productivity was estimated by harvesting a plant every sample point. The attributes studied showed moderate spatial dependence structure, the spherical model being the best fit for all variables. The greatest variability was obtained by productivity in season 1 (CV 66.66%) and the lowest for the season 1 also N (CV 9.21%). Both variables were normally distributed, with a range of 14,31 and 44,0 m, respectively. The coefficient of variation of the micronutrients Fe, Zn, Cu, Mn and B in the two seasons we observed a moderate CV, being in season 1, following 30,77; 19,02; 37,36; 32,75 and 37,21 respectively in season 2 the following 37,62; 32,20; 24,62; 32,30; 17,30 respectively. The coefficient of variation of the micronutrients Fe, Zn, Cu, Mn and B in the two periods was classified as moderate. The K, Ca, Mg and S macronutrients in season 1 were classified as moderate while the N and P showed low CV, then 2 moderate CV was presented by P, Ca, Mg and S and low CV was presented by N and K.